Program Kerja Praktek Social Media Manager di Kawai Music Batam - Tony Wibowo; Wilson Tungli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
Kawai Music School was the music school and music store that located at Ruko Permata Niaga Regency Blok BB No. 1-3, Baloi Indah, Kec. Lubuk Baja, Kota Batam, Kepulauan Riau. To promote the companies Kawai Music Batam using social media like Instagram. For the design the social media content the method used is MDLC (Multimedia Development Life Cycle), also the apps used are canva and photoshop that the result was uploaded at Instagram. The advice for next PkM to focus education content.